Pelatihan Kader Posyandu Serta Penerapan Praktik PHBS sebagai Upaya untuk Mencegah Penyebaran Penyakit - Willia Novita Eka Rini; Dwi Amelia; Muthiah Fauziyyah; Adinda Novita; Al Qohiyulan Tiar; Rangi Media Pebriza; Syauqina Ahza Magfira (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Training Posyandu cadres is one of the strategic steps in increasing the capacity of human resources at the community level to support public health programmes. Clean and Healthy Living Behaviour (PHBS) is one of the efforts that can be done in increasing awareness of clean living and maintaining the health of the community. Hand sanitizer is only used as an alternative when there is no water or soap when travelling or doing activities outside the home. This article aims to improve the understanding of adolescents and posyandu cadres about phbs and hand sanitizer as a substitute for hand washing for disease prevention. The results of the activity showed that counselling on sanitation and environmental hygiene and the provision of hand sanitisers had a positive impact on increasing public awareness, especially posyandu cadres and adolescents in preventing the spread of diseases.